2014
DOI: 10.1097/phm.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound-Guided Anterior and Posterior Approaches for Needle Insertion into the Tibialis Posterior in Hemiplegic Children with Spastic Cerebral Palsy

Abstract: Ultrasonographic guidance is a useful, safe, and accurate tool for needle insertion into the tibialis posterior. Considering the safety window width, this study suggests needle placement at the upper third point of the tibia for the anterior approach and at the midpoint for the posterior approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…In addition, BoNT-A was injected into one or two sites in the TP muscle under US guidance using an anterior approach at the upper third point of the tibia, with doses ranging from 0.9 to 2.8 units/kg (mean± SD=1.73±0.54 U/kg). 28 All children participated for 30 minutes in a standardized physiotherapy program, which included stretching and strengthening of the ankle plantarflexor and gait training following 4 months after the injections. No electrical stimulation or casting was applied.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, BoNT-A was injected into one or two sites in the TP muscle under US guidance using an anterior approach at the upper third point of the tibia, with doses ranging from 0.9 to 2.8 units/kg (mean± SD=1.73±0.54 U/kg). 28 All children participated for 30 minutes in a standardized physiotherapy program, which included stretching and strengthening of the ankle plantarflexor and gait training following 4 months after the injections. No electrical stimulation or casting was applied.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous ultrasonographic investigation of the TP muscle, we suggested that the needle be inserted at the upper third (the point separating the upper third from the middle third) of the tibia for the anterior approach and at the midpoint for the posterior approach. 34 However, those recommendations were derived only from considerations of the safety window sizes observed by ultrasonography. At that time, the comment was made that further study to localize the MEP zones of the TP muscle would be needed to determine the optimal approach for needle insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Diese zeigte eine Überlegenheit der technischen Zielverfahren. Die US-gezielte BT-Injektion des M. tibialis posterior kann von anterior (auf Höhe des Überganges vom oberen zum mittleren Drittel des Unterschenkels) oder von posterior (auf Höhe der Mitte des Unterschenkels) her erfolgen [44]. Eine noch junge, aber vielversprechende Anwendung der US-gezielten BT-Injektion ist das Piriformis-Syndrom, bei der aber ein Konvex-Schallkopf mit etwas niedrigerer Frequenz (5 bis 7,5 MHz) benötigt wird [45].…”
Section: Armmuskulaturunclassified